Virtual Reality and Body Experience: a New Approach to the Treatment of Eating Disorders - Riva, Giuseppe (International Journal of Virtual Reality, 1996)
Eating Disorders, one of the most common pathologies of the occidental society, have long been associated with alterations in the perceptual/cognitive representations of the body. In fact, a large number of studies have highlighted the fact that the perception of one's own body and the experiences associated with it represent one of the key problems of anorexic, bulimic and obese subjects. The effects have a strong influence on therapy effects: severe body representation disturbance is predictive of treatment failure. However, the treatment of body experience problems is not well defined. Two methods are currently in use: the first is a cognitive/behavioral approach aimed at influencing patients' feelings of dissatisfaction; the second is a visual/motorial approach with the aim of influencing the level of bodily awareness. The Virtual Environment for Body Image Modification (VEBIM), a set of tasks aimed at treating body image, tries to integrate these two therapeutic approaches within an immersive virtual environment. This choice not only makes it possible to intervene simultaneously on all of the forms of bodily representations, but it also uses the psycho-physiological effectsprovoked on the body by the virtual experience for therapeutic purposes. This paper describes the VEBIM theoretical approach and its characteristics. It also presents a study on a preliminary sample (60 normal subjects) to test the efficacy of this approach.